Finland’s Health System 2023 Reform: Emphasizing Rural and Population Health - Godard, Grant M; Wilson, Asa B (Archives of Business Research, 2025)
Comparative international health systems is a growing healthcare academic, policy, and practice interest. The New England Journal of Medicine created a series of fifteen articles, each devoted to one country’s health system using the same descriptive, explanatory, and analytic template [1]. To review and compare the Finish health system’s performance, a similar format was used. The study was done during a study-abroad stay in Finland during the health system’s 2023 reform initiative. The country and its care delivery are discussed as a foundation for describing the reform initiative. A comparative table of health system performance monitors is used to review results from the U.S. and Finnish systems.